2003
DOI: 10.1016/s0016-5085(03)80254-8
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori infection induces duodenitis and superficial duodenal ulcer in mongolian gerbils

Abstract: Background: There is no direct evidence for an animal model of Helicobacter pylori induced duodenal ulcer. Aim: In this study we evaluated the roles of bacterial strain and age of experimental animals in induction of duodenitis and duodenal ulcer in Mongolian gerbils after H pylori infection. Methods: Specific pathogen free Mongolian gerbils were inoculated orally with three bacterial strains (H pylori ATCC 43504, TN2GF4, and K-6, a clinical isolate from a patient with gastric cancer in our clinic). These stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 28 publications
2
12
0
Order By: Relevance
“…Gerbils infected with H. pylori develop an antral gastritis/duodenitis that mimics the ulcerogenic form of the human disease (26). Unlike mice but similar to humans, the bacterial cag pathogenicity island seems to be a critical disease determinant in gerbils (27).…”
Section: Discussionmentioning
confidence: 99%
“…Gerbils infected with H. pylori develop an antral gastritis/duodenitis that mimics the ulcerogenic form of the human disease (26). Unlike mice but similar to humans, the bacterial cag pathogenicity island seems to be a critical disease determinant in gerbils (27).…”
Section: Discussionmentioning
confidence: 99%
“…However, strain SS1 is a mutant of H pylori and its virulence is considerably low. Recently, Mongolian gerbils, which has distinct advantages such as high frequency and stability of infection, large colonization of H pylori, longer living suitable for study with long period of time and pathological changes similar to those observed in human with chronic gastritis, have become the predominant animals for preparing H pylori infection model [42][43][44] . In 1999, Chi et al established a stable model of H pylori infection in Mongolian gerbils, which was orally pretreated with alcohol [49] .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that infection model in Mongolian gerbils by oral challenge once with H pylori suspension at the concentration of 1×10 8 CFU of H pylori is stable [42][43][44] . In the present study, H pylori was undetectable in the gastric mucosa from Mongolian gerbils at 2 wk after challenge once with 1×10 8 CFU of the bacterium.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, H. pylori infection is still prevalent in developing countries with high infection rates (4). Not only in underdeveloped countries but also in developed countries, H. pylori infection mostly occurs in childhood, and the chances of a new infection are very rare in adulthood (5). In addition, since the probability that H. pylori infection in childhood is naturally healed is extremely low, most infected patients live their life together with the bacteria (6 (6).…”
Section: Introductionmentioning
confidence: 99%